Differential transcriptional responses underlie dietary induction of intestinal carbohydrase activities in house sparrow nestlings - Gatica Sosa, Claudia (2015)
Many species show diet-induced flexibility of activity of intestinal enzymes; however, molecular and genetic mechanisms responsible for such modulation are less known, particularly in altricial birds. The goal of our study was to test whether a diet-induced increase of activity of intestinal maltase and sucrase in house sparrow nestlings is matched with an increase in maltase-glucoamylase (MG) and sucrase-isomaltase (SI) complex mRNAs, respectively. Both enzyme activities were significantly higher in mid intestine of nestlings fed a medium starch (MS) diet compared to those fed a starch-free (SF) diet. In contrast to the similar pattern of dietary induction for both enzyme activities, diet MS elevated significantly only the level of MG mRNA, but not SI mRNA. The coordinated increase in activity of maltase and in MG mRNA is consistent with the hypothesis that dietary induction of this enzyme is under transcriptional control. In contrast, the lack of such coordination for changes in activity of sucrase and SI mRNA suggests that up-regulation of this enzyme may be achieved by post-translational factor(s). We conclude that genetic mechanisms responsible for diet-induced flexibility of digestive enzymes in birds may differ from that observed in mammals.